Stakeholder acceptance of shared toilets to improve sanitation access in low-income urban settings: a case study of Gulu city, Uganda - Anna Therese Schoell; Rebecca Scott (Journal of Water, Sanitation and Hygiene for Development, 2023)
With growing worldwide urbanisation, ensuring adequate sanitation for all urban citizens is gaining importance. Access to sufficient and appropriate sanitation presents particular challenges for low-income areas of high population density. In Gulu city, Uganda, 87% of the population relies on shared sanitation facilities. This paper investigates under what circumstances shared toilets can offer access to improved sanitation facilities. It explores stakeholders' perceptions of shared toilets – users, political leaders, and key decision-makers of Gulu. Findings are analysed from an existing dataset of over 10,000 households, alongside qualitative data from household interviews, key informant interviews with health inspectors, health workers, political leaders, and focus group discussions. Results reveal that shared toilets have the potential to improve access to enhanced sanitation technology in areas where people lack the space and financial means to construct individual household toilets. For shared toilets to be acceptable, they would be of a higher sanitation technology, located on private land, with the familiarity of users, and agreed cleaning and maintenance regimes. The paper, therefore, proposes improving both the technology and arrangements for the use of shared facilities, to a level that satisfies users and improves access to safe sanitation in low-income urban areas. HIGHLIGHTS The technology of shared toilets can influence cleanliness and hence increase user acceptance.; Users are more willing to share toilets with those they know, such as neighbours or extended family members.; With the right technology, location, access, and maintenance arrangements, shared toilets can improve access to safer forms of sanitation in high-density urban areas.;